Efeitos das β-carbolinas derivadas da ayahuasca sobre as repercussões morfofuncionais do trato gastrintestinal de camundongos submetidos ao estresse físico crônico - Belém, Mônica de Oliveira (2021)
Gastrintestinal (GI) tract is closely related to central nervous system, with repercussions resulting from anxiety disorder, depression and stress. As a new therapeutic approach possibility to these disorders, Ayahuasca appears, but still without evaluating its reflex in GI tract. The objective was to evaluate chronic physical stress (CPS) repercussions on morphology, motility, permeability and contractility of Swiss mice gastrointestinal tract, as well as biological effect of β-carbolines derived from Ayahuasca for treatment of these chanEs. CPS induction occurred over eleven consecutive days by restraining movement (3h/day), followed by solid fasting (12h/dark cycle). The animals were treated (IP) with βcarbolines harmine (HM, 15mg/kg), harmaline (HL, 20mg/kg) or tetrahydroharmine (THH, 1, 10 or 30mg/kg) from fifth to 11th day or prepared from three active ingredients, the pharmahuasca (PH), on fifth and eighth induction day. Survival, body mass, feed and water consumption, body composition, gastric emptying (E) of liquid and solid, in vitro contractility, transepithelial resistance (TERE) and intestinal permeability, and transmural GI tract morphometry were evaluated. The stress per si caused reduced survival, weight loss, inversion of food consumption pattern, intense free fat mass loss and had a dual impact on E, with acceleration in liquids and delay in solid food, associated with gastric antrum lower contractile responsiveness, and duodenum hypercontractility. Associated with this, stress reduces TERE, without altering intestinal permeability. Added to this, thinning of structures lumen closer in small intestine, while in colon, transmural thickening or flattening was observed, region evaluated depending. It was also noted that environment has an important influence on chanEs appearance when animals submitted or not to stress were kept in a shared environment. Finally, vagus-vagal innervation integrity was also found to play a fundamental role in appearance of alterations resulting from CPS. When treated with β-carbolines derived from Ayahuasca, it was noted that, despite sharing the same pharmacological action mechanism, each treatment and whether administered alone or in a pharmahuasca preparation, respond differently to chanEs in the GI tract of animals under CPS. FH per si apparently does not alter E basal functioning, whereas in a stressful situation, it causes EG of liquids and solids delays, associated with lower gastric antrum and duodenal responsiveness to pharmacomechanical and pharmacochemical stimuli. The repercussion in E to THH was dose dependent, since in a low dose (1 mg/kg) it regulates E of liquid rate, whereas in an intermediate dose (10 mg/kg) it causes acceleration and in a high dose (30 mg/kg) delay this phenomenon. On the other hand, treatment with HM or HL was able to abolish E chanEs, caused by CPS, inducing less gastric fundus and antrum contractile responsiveness. Thus, it is concluded that β-carbolines derived from Ayahuasca can be considered in treatment of repercussion of chronic physical stress on the gastrointestinal tract.